2007
DOI: 10.1001/jama.297.23.2587
|View full text |Cite
|
Sign up to set email alerts
|

Limited Family Structure and BRCA Gene Mutation Status in Single Cases of Breast Cancer

Abstract: ERMLINE BRCA1 OR BRCA2 gene mutations significantly increase a woman's risk of breast cancer (50%-85%) and ovarian cancer (16%-50%). 1-5 Identifying women who have had BRCAassociated breast cancer is important because the risk of a new primary breast cancer within 10 years following initial diagnosis is as high as 40% in the absence of oophorectomy or tamoxifen treatment. 6 The corresponding 10-year risk of ovarian cancer is also substantial (6%-12%). 7 Limited-stage breast cancer patients who carry a BRCA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(95 citation statements)
references
References 35 publications
2
90
1
2
Order By: Relevance
“…Weitzel et al 15 reported an AUC of 0.67 for the BRCAPRO model in women with breast cancer who did not have any first-or second-degree relatives with breast or ovarian cancers. We observed a similar finding in the current cohort.…”
Section: 37mentioning
confidence: 99%
See 1 more Smart Citation
“…Weitzel et al 15 reported an AUC of 0.67 for the BRCAPRO model in women with breast cancer who did not have any first-or second-degree relatives with breast or ovarian cancers. We observed a similar finding in the current cohort.…”
Section: 37mentioning
confidence: 99%
“…[5][6][7][8] Of these, the BRCAPRO model has been widely used and extensively evaluated, mostly in non-Hispanic white populations. [9][10][11][12][13][14][15][16] This model, like other carrier prediction tools, was developed on the basis of mutation rates and penetrances observed mainly in women of Ashkenazi Jewish and European ancestry. To our knowledge, no large study has evaluated the utility of the BRCAPRO…”
Section: Introductionmentioning
confidence: 99%
“…In a study of young patients with breast cancer, 50% of those who were found to be carriers of BRCA1/BRCA2 had no immediate family history of cancer. 18 Therefore early detection and intROdUctiOn BRCA1 and BRCA2 are the major genes known to be involved in hereditary breast and ovarian cancers. The frequency of BRCA mutations in the general population is epidemiologically estimated at 0.06 to 0.26%.…”
mentioning
confidence: 99%
“…This might partially have taken limited family structure into account. However, limited family structure per se (24) was not examined in any of the studies.…”
Section: Family History Assessment Including Reliance On National Damentioning
confidence: 99%